Assessment of perceived stress levels and its sources among indian students in Dental Colleges of Odisha - A cross-sectional study - Sonali Sarkar; Dhirendra Kumar Singh; Riddhi Awasthi (Wolters Kluwer Medknow Publications, 2022)
Background: Dental school is a stressful experience for students as they face wide-ranging challenges related to patient care and pursuing academic excellence. Aim: The aim of the study is to estimate the psychological stress levels and its sources among undergraduate students at dental colleges in India. Materials and Methods: A cross-sectional survey was conducted among a sample of 308 undergraduate students in their 3rd year, 4th year, and internship from three private dental schools in Odisha. A self-administered questionnaire was designed and distributed where participants marked the stress levels caused by various academic and nonacademic stressors on a five-point Likert scale (strongly disagree to strongly agree). Demographic data of gender and year of study were also collected on the same questionnaire. Statistical Analysis Used: SPSS v27 was used to compute descriptive statistics, to perform tests for reliability and validity of the survey instrument and to perform two sample t-test for comparison of stressors with gender and one-way ANOVA for comparison of stressors year of study as factors. Results: Of the 300 completed questionnaires submitted, 49.7% of the participants were males (n = 151) and 50.3% were females (n = 149). Third-year students reported moderate stresses (mean stress >=3) due to factors related to curriculum structure, long classroom hours, reduced recreation time, homesickness, and hostel food. Fourth-year students reported severe stress (mean stress >=4) originating from stressors like completion of clinical quota and comparison with other professions. Interns reported severe stress (mean stress >=4) originating from stressors like family's expectations and fear of failure. There was a statistically significant difference in female participants who reported elevated stress compared to their male counterparts in dealing with stress related to workload and training (P = 0.008, two-tailed two-sample t-test). Conclusions: Students reported most stress originating from issues related to clinical workload burden, comparison with peers, family expectations, and personal relationship issues. We recommend that dentistry schools act with urgency to alleviate severe stressors with the formation of student advisory committees and appointment of counselors who can advocate for dental students' psychological well-being.